Renforcer les capacités des systèmes semenciers pour accélérer l’adoption des variétés améliorées de haricot en Afrique de l’Est, centrale et australe - Rubyogo, Jean-Claude (Centre de coopération internationale en recherche agronomique pour le développement, 2006)
Strengthening local seed systems for wider utilization of improved bean varieties: experiences in eastern, central and southern Africa. Beans (Phaseolus vulgaris L.) are important for food security and as cash crops in eastern, central and southern African regions. Despite a considerable number of adapted varieties developed and released by national agricultural research services (NARSs) in collaboration with the International Centre for Tropical Agriculture (CIAT), a few of them are cropped by farmers on limited areas. An initiative based on partnerships between NARSs, extension service providers, commercial seed companies, farmers and their organisations was launched to boost the utilization of improved bean varieties, therefore broadening the impact. As a result of that partnership, there is more joint planning, sharing of responsibilities among partners and subsequently more farmers are gaining greater access to improved bean varieties.